Community Empowerment Dynamics of Masjid-Based Bayt al-Mal: A Phenomenology Approach - Aditya Pratama (Universitas Pembangunan Nasional Veteran Jakarta, 2023)
Historically, masjids were the center of government, education, and economy. Nowadays there is an impression that Muslims are only busy to build the physical masjid and are not familiar with reality because Muslims tend to prioritize ceremonial rituals and underestimate the social functions of masjids. This study aims to assess the above assumptions and provide an overview of analytical reviews in capturing the phenomena of the management of masjid-based bayt al-mal. Thus, it can be well recognized the sides of excellence and weaknesses that may exist. This research uses qualitative methods with a phenomenological approach. The research found that there are four phenomena of management of masjid-based bayt al-mal in the Special Province of Yogyakarta namely providing people with social funds through bayt al-mal, empowering people through bayt al-mal, empowering communities not through bayt al-mal. This research emphasizes the evolving roles of masjids, extending beyond mere places of worship. The effectiveness of these multifaceted roles hinges on strong financial management, active fundraising, and transparent utilization of bayt al-mal funds. Training and professional management are also crucial for optimizing resources and building community trust. Masjids can serve as centers of community empowerment and positive social change when embracing their broader roles and responsibilities. Secara historis, masjid adalah pusat pemerintahan, pendidikan, dan perekonomian. Saat ini ada kesan umat Islam hanya sibuk membangun fisik masjid dan tidak paham dengan kenyataan karena umat Islam cenderung mengutamakan ritual seremonial dan meremehkan fungsi sosial masjid. Penelitian ini bertujuan untuk mengkaji asumsi-asumsi di atas dan memberikan gambaran tinjauan analitis dalam menangkap fenomena pengelolaan masjid berbasis bayt al-mal. Dengan demikian, dapat diketahui dengan baik sisi keunggulan dan kelemahan yang mungkin ada. Penelitian ini menggunakan metode kualitatif dengan pendekatan fenomenologis. Penelitian ini menemukan bahwa terdapat empat fenomena pengelolaan bayt al-mal berbasis masjid di Daerah Istimewa Yogyakarta yaitu pemberian dana sosial kepada masyarakat melalui bayt al-mal, pemberdayaan masyarakat melalui bayt al-mal, pemberdayaan masyarakat tidak melalui bayt al-mal, -mal. Penelitian ini menekankan perubahan peran masjid, tidak hanya sekedar tempat ibadah. Efektivitas peran multifaset ini bergantung pada pengelolaan keuangan yang kuat, penggalangan dana yang aktif, dan pemanfaatan dana bay al-mal yang transparan. Pelatihan dan manajemen profesional juga penting untuk mengoptimalkan sumber daya dan membangun kepercayaan masyarakat. Masjid dapat berfungsi sebagai pusat pemberdayaan masyarakat dan perubahan sosial yang positif ketika menjalankan peran dan tanggung jawab mereka yang lebih luas.